1986
DOI: 10.1099/0022-1317-67-1-119
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Structure of Transmissible Gastroenteritis Virus. I. Properties of Monoclonal Antibodies Directed against Virion Proteins

Abstract: SUMMARYThirty-two hybridoma cell lines producing monoclonal antibodies (MAbs) against the three major structural proteins of transmissible gastroenteritis virus (TGEV) have been isolated. Radioimmunoprecipitation of intracellular viral polypeptides showed that 17 hybridomas recognized both the peplomer protein [E2, 220 × 10 3 tool. wt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
107
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(116 citation statements)
references
References 25 publications
9
107
0
Order By: Relevance
“…We have recently reported the derivation of MAbs directed against the three major structural polypeptides of TGEV and confirmed that all essential neutralization-mediating determinants were carried by the 220K glycoprotein E2 (Laude et al, 1986). As was observed in the case of MHV4 (Wege et al, 1984), all the 17 MAbs which recognized E2 also immunoprecipitated its intracellular precursor (E'2, 175K), whereas six other MAbs selectively recognized the 175K species.…”
Section: -7169 © 1986 Sgmmentioning
confidence: 89%
See 2 more Smart Citations
“…We have recently reported the derivation of MAbs directed against the three major structural polypeptides of TGEV and confirmed that all essential neutralization-mediating determinants were carried by the 220K glycoprotein E2 (Laude et al, 1986). As was observed in the case of MHV4 (Wege et al, 1984), all the 17 MAbs which recognized E2 also immunoprecipitated its intracellular precursor (E'2, 175K), whereas six other MAbs selectively recognized the 175K species.…”
Section: -7169 © 1986 Sgmmentioning
confidence: 89%
“…The preparation of MAbs, as well as their characterization with respect to polypeptide specificity (E2 and/or E'2) and neutralizing ability have recently been published (Laude et al, 1986). Immunoglobufins (Igs) from ascites fluids were purified by gel permeation as already described (Laude et al, 1986), and stored at -20°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An independent group of recent isolates from TGE field outbreaks (S387, T232, T507, T517, T988, U328 and CC717) was different from the historical Miller and Purdue types. Although only one serotype of TGEV was described [22], it has been suggested that antigenic variation of TGEV may occur in nature [17,25,44,52]. Delmas et al [6] reported that four antigenic sites (A, B, C and D) of TGEV are located on the N-terminal half of the S glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…Site C was composed of largely conformationindependent epitopes and showed slight variation among TGEV strains [6]. Epitopes involved in the antigenic variation of TGEV strains have been found outside the major neutralization domain and induced non-neutralizing antibodies [25,41]. However, these MAbs bound to wide range of TGEV strains.…”
Section: Discussionmentioning
confidence: 99%